Association between hypertension and risk of knee osteoarthritis: A meta-analysis of observational studies. Issue 32 (August 2017) - Zhang, Yi-min; Wang, Jun; Liu, Xiao-guang
Abstract : Abstract: Evidence from observational studies shows that hypertension may be a risk factor for knee osteoarthritis (OA). However, the relationship between hypertension and knee OA risk remains controversial. This study aimed to quantitatively assess the relationship between hypertension and risk of knee OA. Three electronic databases (PubMed, Embase, and Cochrane Library) were searched up to July 25, 2016. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were extracted from the included observational studies. Publication bias, heterogeneity test, and subgroup analyses were performed. Eight studies including 2 cohort studies and 6 cross-sectional studies with 9762 participants were finally included in this meta-analysis. The results showed that hypertension was significantly associated with higher radiographic knee OA and symptomatic knee OA risks of 2.01 (95% CI, 1.28–3.15, I 2 = 90.2%, P for heterogeneity <.001) and 1.49 (95% CI, 1.26–1.77, I 2 = 0%, P for heterogeneity <.412), respectively. No publication bias was detected. The subgroup analysis showed that the study design did not influence the results (radiographic knee OA: OR = 1.42, 95% CI, 1.19–1.71 for cross-sectional studies and OR = 2.17, 95% CI, 1.30–3.63 for cohort studies; and symptomatic knee OA: OR = 1.85, 95% CI, 1.10–3.13) for cross-sectional studies and OR = 2.74, 95% CI, 1.81–4.16 for cohort studies). This meta-analysis showed that there was a significant relationship between hypertension and knee OA (both radiographic and symptomatic). However, further original studies are needed that use a better design.